Pengaruh Ukuran Perusahaan dan Reputasi Kantor Akuntan Publik (KAP) terhadap Biaya Auditor Eksternal (Studi pada Perusahaan yang Terdaftar pada Indeks LQ-45 Tahun 2017) - Cahyaningsih, Yuliana Duwi (IAIN Surakarta, 2018)
This research aims to determine the influence of company size and the reputation of the Public Accountant Office (KAP) on the cost of external auditors. The independent variables in this study were the company size and reputation of the KAP while the dependent variables in this study were the costs of external auditors. With a quantitative approach, hypotheses in the study were tested using linear regression analyses. Using the purposive sampling, 30 companies became samples in this study. Results of this study showed that the company size and reputation of KAP did not affect the costs of external auditors of the company.Keywords: firm size, auditor reputation, audit fee.